Optymalizacja treningu sportowego w piłce nożnej na przykładzie piłkarzy IV ligowego zespołu „Grom Osie” = Optimization of sports training in football for example IV football league team, "Grom Osie" - Stankiewicz, Błażej Stanisław; Środa, Jakub (Journal of Education, Health and Sport, 2017)
Stankiewicz Błażej, Środa Jakub. Optymalizacja treningu sportowego w piłce nożnej na przykładzie piłkarzy IV ligowego zespołu „Grom Osie” = Optimization of sports training in football for example IV football league team, "Grom Osie". Journal of Education, Health and Sport. 2016;6(11):473-499. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.188112 http://ojs.ukw.edu.pl/index.php/johs/article/view/4024 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016. Optymalizacja treningu sportowego w piłce nożnej na przykładzie piłkarzy IV ligowego zespołu „Grom Osie” Optimization of sports training in football for example IV football league team, "Grom Osie" Błażej Stankiewicz¹, Jakub Środa¹ Blazej Stankiewicz¹, Jakub Sroda¹ ¹Uniwersytet Kazimierza Wielkiego w Bydgoszczy ¹Kazimierz Wielki University in Bydgoszcz Badania statutowe BS/2016/K19 IKF/WKFZiT/UKW Słowa kluczowe: piłka nożna, trening szybkości, test Rast Key words: football, speed training, Rast test Streszczenie W ostatnich dziesięcioleciach nastąpiły olbrzymie zmiany w grze w piłę nożną. Zwiększyło się tempo gry, zmieniły się: styl gry, technika, taktyka, a także przepisy. W czasie meczu zwodnicy wykonują około 1000 różnych czynności ruchowych, które zmieniają się średnio co 6 sekund (Rynkiewicz i Niewolna, 2011). Osiągnięcie takiego poziomu wymaga realizacji regularnego i racjonalnie przygotowanego procesu treningowego. Do tych zmian musiał dostosować się trening piłkarski, poważne zmiany nastąpiły w jego teorii i metodyce (Chmura i in., 2008). Przygotowanie motoryczne piłkarzy do okresu startowego obejmuje dziś inny zakres, inne środki i metody. Z fizjologicznego punktu widzenia zawodnik podczas meczu poddany jest dużemu wysiłkowi wytrzymałościowemu, w którym źródłem energii są procesy aerobowe i anaerobowe (Jurkowski i Wysocki, 2011). Celem pracy była weryfikacja skuteczności przeprowadzonego eksperymentu za pomocą analizy porównawczej wyników testów o charakterze beztlenowym przeprowadzonych wśród zawodników trenujących piłkę nożną w IV ligowym Klubie Grom Osie na początku i na końcu okresu przygotowawczego. Analizując badaną populację stwierdzić jednoznacznie można, że ich przygotowanie w sferze przemian beztlenowych stoi na bardzo dobrym jak na warunki IV ligi rozgrywkowej warunki. Średnia wartość czasu uzyskanego w biegu na 20 m wyniosła 3,181 sek. Próba mocy maksymalnej i pomiaru spadku mocy, prowadzona za pomocą testu „Rast” ukazała wynik średni mocy maksymalnej zawodników „Gromu” rzędu 13,4 W/kg i jest t rezultat lepszy od napotkanych w piśmiennictwie. Summary In recent decades there have been huge changes in the game of football. Increased pace of the game have changed: playing style, technique, tactics, and rules. During the match, players carry about 1,000 different motor actions, which change every 6 seconds (Rynkiewicz i Niewolna, 2011). Achieving this level requires the implementation of regular and reasonably prepared training process. These changes have to adapt to football training, major changes took place in the theory and methodology (Chmura i in., 2008). Preparing motor players to the tournament period today has a different range, other means and methods. From a physiological point of view of a player during the match it is subject to a large effort of endurance, where the source of energy are aerobic and anaerobic processes (Jurkowski i Wysocki, 2011). The aim of the study was to verify the effectiveness of the experiment by means of a comparative analysis of the test results of an anaerobic carried out among competitors practicing football in the fourth league club Grom Osie at the beginning and at the end of the preparatory period. Analysing the population can say unequivocally that their preparation in the field of anaerobic stands on very good terms for the fourth league form conditions. The average value of time obtained in the course of 20 m was 3,181 sec. Attempting to maximum power and measuring the decrease in power, led by the test "Rast" was released the result of the average maximum power players "Thunder" of the order of 13.4 W / kg and t is the result of better than encountered in the literature.